Strong Suppression of Thermal Conductivity in the Presence of Long Terminal Alkyl Chains in Low‐Disorder Molecular Semiconductors. Issue 37 (3rd August 2021) - Selezneva, Ekaterina; Vercouter, Alexandre; Schweicher, Guillaume; Lemaur, Vincent; Broch, Katharina; Antidormi, Aleandro; Takimiya, Kazuo; Coropceanu, Veaceslav; Brédas, Jean‐Luc; Melis, Claudio; Cornil, Jérôme; Sirringhaus, Henning
Abstract: While the charge transport properties of organic semiconductors have been extensively studied over the recent years, the field of organics‐based thermoelectrics is still limited by a lack of experimental data on thermal transport and of understanding of the associated structure–property relationships. To fill this gap, a comprehensive experimental and theoretical investigation of the lattice thermal conductivity in polycrystalline thin films of dinaphtho[2, 3‐b:2′, 3′‐f]thieno[3, 2‐b]thiophene (C n ‐DNTT‐C n with n  = 0, 8) semiconductors is reported. Strikingly, thermal conductivity appears to be much more isotropic than charge transport, which is confined to the 2D molecular layers. A direct comparison between experimental measurements (3ω–Völklein method) and theoretical estimations (approach‐to‐equilibrium molecular dynamics (AEMD) method) indicates that the in‐plane thermal conductivity is strongly reduced in the presence of the long terminal alkyl chains. This evolution can be rationalized by the strong localization of the intermolecular vibrational modes in C8‐DNTT‐C8 in comparison to unsubstituted DNTT cores, as evidenced by a vibrational mode analysis. Combined with the enhanced charge transport properties of alkylated DNTT systems, this opens the possibility to decouple electron and phonon transport in these materials, which provides great potential for enhancing the thermoelectric figure of merit ZT . Abstract : A significant drop in in‐plane thermal conductivity upon end alkylation of the aromatic rings of dinaphtho[2, 3‐b:2′, 3′‐f]thieno[3, 2‐b] thiophene (DNTT), which is understood from a detailed vibrational‐mode analysis, is identified via a comprehensive experimental and theoretical investigation. Combined with their enhanced charge transport, the results suggest the possibility of decoupling electron and phonon transport in alkylated DNTT systems, which opens pathways for improved thermoelectric applications.